2018
DOI: 10.3390/jrfm11040085
|View full text |Cite
|
Sign up to set email alerts
|

Assessment of Upstream Petroleum Fiscal Regimes in Myanmar

Abstract: This study aims to assess Myanmar’s upstream petroleum fiscal regimes by applying comprehensive indicators to rank the level of attractiveness of Myanmar. The indicators include government take (GT), front loading index (FLI), and composite score (CS). The decision maker’s attitude for GT and FLI were considered in CS linear weighting method in ranking the fiscal terms attractiveness. The results showed that Myanmar’s upstream petroleum fiscal regime has low attraction compared to its competing countries from … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
2
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 12 publications
(5 citation statements)
references
References 23 publications
0
2
0
Order By: Relevance
“…Government take for Canada, the United States, and Australia are 58.36%, 72.74%, and 43.92% respectively, and their royalties are 27.5, 20%, and 6.25% respectively; while tax rates are 15%, 35%, and 30% (Phillips, 2008). Literature has shown that Australian petroleum fiscal policy is more attractive (Kraal, 2017;Swe and Emodi, 2018). Australia allows for accelerated depreciation, immediate write off of exploration expenditure, research and development (R&D) incentive, and expenditure uplift.…”
Section: Fiscal Regime Elementsmentioning
confidence: 99%
“…Government take for Canada, the United States, and Australia are 58.36%, 72.74%, and 43.92% respectively, and their royalties are 27.5, 20%, and 6.25% respectively; while tax rates are 15%, 35%, and 30% (Phillips, 2008). Literature has shown that Australian petroleum fiscal policy is more attractive (Kraal, 2017;Swe and Emodi, 2018). Australia allows for accelerated depreciation, immediate write off of exploration expenditure, research and development (R&D) incentive, and expenditure uplift.…”
Section: Fiscal Regime Elementsmentioning
confidence: 99%
“…One of the most important aspect of petroleum tax system is the government take (Swe and Emodi, 2018). It is defined as the "proportion of the host nation's income from investment project to the total project revenue within the valid period of the contract" (Luo and Yan, 2010:758).…”
Section: Hypothesis Developmentmentioning
confidence: 99%
“…Financial term in fossil sector draws investors, ensuring fair economic performance and cost balance (Mardiana et al, 2019;Yun et al, 2020). This includes oil and gas exploration, production, and distribution laws, terms, and taxes (Swe & Emodi, 2018;Ghosh et al, 2020).…”
Section: Introductionmentioning
confidence: 99%